Public Attitudes Toward Fiscal Programs - Mueller, Eva (Quarterly Journal of Economics, 1963)
I. Sample surveys as a tool for measuring attitudes toward fiscal policies, 211. — II. Some survey findings, 213. — III. The congruence and stability of fiscal preferences, 223. — IV. Group differences in attitudes toward fiscal policies, 228.